Assistance in Planning and Implementing Educational Activities for Elementary School Students and The Community about Adequate Villages for Clean Water And Sanitation of Stunting Prevention According to Sustainable Development Goals (SDGs) in Pindahan Bar - Annisa Annisa (UMBanjarmasin, 2023)
The right intervention in handling and reducing stunting is nutrition-sensitive intervention. Nutrition-sensitive interventions intervene in the causes of stunting by improving sanitation and increasing the supply of clean water through a community-based clean water supply system so that access to proper sanitation and access to clean water, especially safe drinking water. Pindahan Baru Village, Rantau Badauh Sub-district is one of the locations that is a priority group for the acceleration of stunting prevention in Barito Kuala Regency with clean water and sanitation problems that can be said to be inadequate because it is still oriented towards the use of river water and floating latrines. Therefore, the purpose of this activity is to provide understanding and direction on the importance of environmental conditions, namely the lack of access to clean water and proper sanitation facilities and aspects of unqualified latrines that greatly affect the incidence of stunting. The method used in this activity is assistance in planning work programs carried out in the village and their implementation directly in the field which aims to educate directly to elementary school students and community leaders, village officials, and the community in Pindahan Baru Village. Assistance in planning and implementing the education resulted in an agreement that the Clean Water and Sanitation Decent Village based on the Sustainable Development Goals (SDGs) Program is closely related to efforts to accelerate stunting prevention in Pindahan Baru Village, Rantau Badauh District.